Inclusive HIV Prevention in South Africa: Reaching Foreign Migrant Adolescent Girls - Temin, Miriam; Milford, Cecilia; Beksinska, Mags; Van Zyl, Debbie; Cockburn, Jonathan (Frontiers in Reproductive Health, 2021)
Within South Africa’s HIV epidemic, foreign migrant adolescent girls and young women (AGYW) face unique challenges in an environment typified by xenophobia and structural inequity. The intersection of age, gender, and migrant-related factors create threats that may exacerbate their HIV risk, including discrimination, limited social capital, and economic dependency. This paper explores HIV-related determinants of risk from the perspective of foreign migrant AGYW who participated in a Girls’ Club project implemented by Community Media Trust. Within clubs, foreign migrant AGYW met weekly with a female mentor to discuss HIV, safety planning, financial literacy, and other topics. Focus group discussions (FGDs) were conducted with club members and parents to learn about pressing challenges in a context characterized by early sexual debut, high rates of teenage pregnancy, and relationships typified by material exchange. FGDs addressed HIV risk factors such as social isolation and limited access to services, exacerbated by migrant-related stigma and discrimination and lack of identity documents. The AGYW appreciated the role of the Girls’ Clubs and mentors in helping foreign migrant AGYW overcome barriers to school and health services as well as building their social and other assets. FGD results indicate that HIV prevention in South Africa should prioritize action to address the specific determinants of foreign migrant AGYW’s HIV risk, as well as inclusive policies that recognize migrants’ heterogeneity based on gender and age.